Calf lengthening may improve knee recurvatum in specific children with spastic diplegic cerebral palsy. (2020) - Bauer, Jeremy; Do, K. Patrick; Feng, Jing; Aiona, Michael
Abstract: Purpose: Knee hyperextension in stance is a difficult condition to treat in children with spastic diplegic cerebral palsy (CP). In children with passive knee hyperextension, the presence of contracture or spasticity of the calf leads to knee hyperextension in stance phase. We hypothesize surgical treatment of the contracture of the calf will lead to less knee hyperextension. Methods: We performed a retrospective review of children who were evaluated in our movement laboratory over 23 years with a diagnosis of CP Gross Motor Function Classification System I, II or III. We selected children who had passive knee hyperextension on exam and who underwent calf lengthening surgery. Children were divided into two groups: early recurvatum (ER) (n = 20) and late recurvatum (LR) (n = 14). Results: There was no difference in the preoperative passive knee extension among the groups or the surgeries performed. For children who had passive knee hyperextension, calf lengthening improved static dorsiflexion with knee flexion on clinical exam by 9.3° in the ER group, 9.6° in the LR group as well as dorsiflexion with knee extension on clinical exam by 9.5° in the ER group and 6.4° in the LR group. The kinematic data showed that the ER group improved their knee hyperextension by 11° (p < 0.001), whereas the LR group did not significantly change their stance phase knee position. Conclusion: Children with passive knee hyperextension who have a calf contracture and walk in knee hyperextension in the first half of stance phase may improve after calf lengthening. Level of Evidence: III